Myocellular limitations of human performance and their modification through genome-dependent responses at altitude - Flueck, M. (Experimental Physiology, 2010)
Human muscle operates along a continuum of power output, which is set through bioenergetic and anatomical principles. In turn, environmental and intrinsic factors during contractile work exert pronounced control over muscle performance by instructing muscle remodelling. This phenotypic control is specifically indicated with intense exercise at altitude, when extra strain is put on energy supply and the temperature-dependent mechanical efficiency of contraction. While it is classically thought that chronic exposure to hypoxia is maladaptive, repeated short episodes of reduced oxygenation alone or in combination with intense endurance work is now understood to preserve exercise performance when atmospheric oxygen levels are low. Endurance training at moderate altitude exploits the temperature-dependent malleability of energy supply that may maximize metabolic flux at altitude. The contribution of genomic mechanisms is important to the plasticity of metabolic pathways in exercised muscle. This is highlighted by the association of distinct gene polymorphisms in master governors of mitochondrial and vascular growth with exercise phenotypes. Feedforward control of human locomoter muscle by exercise involves the transient upregulation of transcript expression for metabolic processes. The response of the mitochondrial transcriptome to intense exercise is graded with respect to mitochondrial content and deoxygenation during muscle work and reflects exercise-induced mitochondrial biogenesis. This supports the notion that genome-mediated muscle malleability is under feedback control by design constraints of the pathway of oxygen. Thus, activity-dependent and genetic mechanisms contribute to the interindividual difference in the metabolic bottlenecks in athletes performing in exceptional environmental conditions.